Effects of pre-treatment and bioaugmentation strategies on the anaerobic digestion of chicken feathers - Costa, J. C. (2012)
Anaerobic digestion of raw chicken feather waste and its co-digestion with poultry litter were assessed in batch assays. Following, two strategies were evaluated to improve methane production from chicken feathers: (i) waste pre-hydrolysis through thermochemical treatment using lime and sodium hydroxide, and (ii) amendment of digestion broth with the proteolytic bacterium Fervidobacterium pennivorans. Anaerobic digestion of the raw waste (2.5% total solids) allowed a specific methane production of 123 ± 3 L CH4 kg 1 VS. Pre-treatment and bioaugmentation strategies did not improve methane production from feather waste, despite the significant increase in waste solubilisation, from 45 ± 5% up to 64 ± 1% using F. pennivorans and up to 96% after pre-treatment with 2 g NaOH g 1 waste. These results indicate that conversion of soluble organic matter to methane, and not the hydrolysis rate, was the limiting step for the anaerobic digestion of chicken feather waste.